Cover girl [compact disc] - Watson, Aaron, 1977- (Adub Records, 2023)
Inspired by talks with his 13-year-old daughter, Jolee Kate, about powerful female artists, singers, and songwriters, Aaron Watson is proud to deliver Cover Girl. A bold move for a Texas-based artist steeped in the roots of country music, these 11 genre-bending cover songs go from Dolly Parton and Rosanne Cash to the Pretenders and Lady Gaga, with Emmylou Harris, Sheryl Crow, and Taylor Swift songs thrown in for good measure.